Carbon emission and cost of blockchain mining in a case of peer-to-peer energy trading - Coutinho, Kevin; Wongthongtham, Pornpit; Abu-Salih, Bilal; Abu Saleh, Mousa A.; Khairwal, Neeraj Kumari (Frontiers in Built Environment, 2022)
Blockchain is an emerging technology that has demonstrated great uptake potential in Peer-to-Peer (P2P) energy trading. The revolution of blockchain brings substantial benefits and innovation to sustainability energy transitions through P2P trading. Blockchain enables energy commodities to be traded. However, perceptions of the impact this technology have on the environment and its associated costs have garnered recent negative publicity. The aim of this study is to investigate the interconnections between blockchain technology and energy systems, in terms of blockchain electricity consumption against blockchain benefit over renewable energy transitions through P2P energy trading. The energy consumed and carbons emitted from the blockchain validation process is quantified and the cost of blockchain is calculated to determine its economic value in a P2P energy trading case. Real data from operating P2P energy trading systems is used and various insights into the transformation of P2P energy trading using different blockchain scalability solutions are also provided.